Tinjauan Literatur Sistematis: Konsep Moderasi Beragama Dalam Tradisi Pesantren di Jawa - Mujiburrohman, Mujiburrohman (PAKAR Pendidikan, 2024)
Pesantren is a stronghold for the entry of radicalism and prevents the degradation of a nation's morality. A critical aspect of the tradition of pesantren is the competence of religious moderation, which must be continuously improved. The study uses a systematic literature review (SLR) method to analyze the concepts of religious moderation that are evolving and becoming a tradition in the Javanese pesantren. There are 16 articles that meet the quality assessment from 4,252 types of documents in the form of scientific journal articles. Researchers used the Dimensions database as a data source. The results of this study show that the concept of religious moderation used in the pesantren tradition in Java includes: teaching national values, social empowerment, moderation values in worship practices, interfaith dialog, charismatic kyai (pesantren leader), openness to modern science and understanding of local wisdom. In its implementation, the pesantren strengthens the competence of religious moderation by improving holistic education, training moderate preachers, developing digital media, developing education, interfaith dialog activities, and building social care. Understanding this concept will affect the pesantren tradition, especially Java, including the attitude of active participation in social programs, upholding Islamic values and local culture, preventing radicalism, encouraging innovation in the education system, increasing tolerance and unity among people, and being critical of extremism.